Improvement of Emotional Response to Negative Stimulations With Moderate-Intensity Physical Exercise - Long, Zhengji; Liu, Guangyuan; Xiao, Zhangyan; Gao, Pengfei (Frontiers in Psychology, 2021)
It is generally accepted that physical exercises not only are good for fitness, but also contribute to mental health and wellbeing. The positive influence of physical exercises on emotion has become a topic of much excitement. However, there is a lack of quantitative study on how the brain activity of emotion is influenced positively by physical exercises. This study is to quantitatively investigate the effect of short-term moderate intensity physical exercise on emotional response by using electroencephalogram (EEG) asymmetry. The experiments including 20-minute moderate intensity cycling and EEG data acquisition with picture-induced emotion assessment protocol were designed in this paper. The experiment procedure consists of two emotion assessment sessions, each of which contains 24 pictures. 80 participants were randomly allocated into the exercise group and the control group. Participants in the exercise group were instructed to have a 20 minutes moderate intensity cycling after the first session, and then they rested until their heart rates recovered to baselines and entered into the second session. The control group only had a 20 minutes break between the two sessions. In the control group, the EEG asymmetry index was not of significant difference between the two assessment sessions for positive and negative stimulations. However, in the exercise group, the difference of the EEG asymmetry index before and after physical exercise was significant only in response to negative stimulations. Further it can be found from comparison for individuals that the short-term moderate intensity physical exercise has a positive impact observed from the change of asymmetry index in response to negative stimulations. The result shows that the negative emotion experience is reduced by the moderate intensity physical exercise, and thus moderate intensity physical exercise is a good alternative for improving emotional response to negative stimulations.